2010
DOI: 10.1029/2009gl041888
|View full text |Cite
|
Sign up to set email alerts
|

Off‐fault plasticity favors the arrest of dynamic ruptures on strength heterogeneity: Two‐dimensional cases

Abstract: [1] We study the effects of a plastic behavior of the volume around the fault on in-plane and anti-plane 2D rupture dynamics. Both rupture modes exhibit similar answer to off-fault yielding, in terms of modification of the kinematics of the rupture front, and in terms of energy lost outside the fault plane. We then compare the ability of the rupture to propagate through a barrier on the interface. The plastic behavior, responsible for a linear increase of the global fracture energy during dynamic crack growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…Considering the saturation of rupture speed, this equation shows that the size of the process zone also saturates, as reported in numerical simulations by Hok et al [2010]. It is Figure 10.…”
Section: Limits On Rupture Speed and Cohesive Zone Sizesupporting
confidence: 65%
See 1 more Smart Citation
“…Considering the saturation of rupture speed, this equation shows that the size of the process zone also saturates, as reported in numerical simulations by Hok et al [2010]. It is Figure 10.…”
Section: Limits On Rupture Speed and Cohesive Zone Sizesupporting
confidence: 65%
“…Combining equations to leads to cμδcA(vr)(1ν)τD.Considering the saturation of rupture speed, this equation shows that the size of the process zone also saturates, as reported in numerical simulations by Hok et al []. It is significant that the Lorentz contraction of the process zone is prevented in self‐similar ruptures in viscoplastic media despite the growth of the outer‐scale stress intensity factor K with rupture distance.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of observations support this suggestion, in which significant coseismic failure and strain occurs around large earthquake ruptures [Fialko et al, 2002;Fialko, 2004;Hamiel and Fialko, 2007;Cochran et al, 2009;Fielding et al, 2009]. Experimental and theoretical models have also been developed recently to examine whether off-fault coseismic damage could emerge from the dynamic rupture process [Harris and Day, 1997;Lyakhovsky et al, 1997;Yamashita, 2000;Poliakov et al, 2002;Dalguer et al, 2003;Rice et al, 2005;Andrews, 2005; Ben-Zion and Shi, 2005;Ando and Yamashita, 2007;Bhat et al, 2007;Templeton and Rice, 2008;Biegel et al, 2008;Viesca et al, 2008;Dunham and Rice, 2008;Duan and Day, 2008;Ma, 2008;Sammis et al, 2009;Dieterich and Smith, 2009;Finzi et al, 2009;Bhat et al, 2010;Biegel et al, 2010;Ma and Andrews, 2010;Shi et al, 2010;Hok et al, 2010;Savage and Cooke, 2010;Dunham et al, 2011aDunham et al, , 2011bXu et al, 2012aXu et al, , 2012bNgo et al, 2012;Suzuki, 2012;Xu and Ben-Zion, 2013;Gabriel et al, 2013]. Although they are based on different formalisms, all these models confirm that significant coseismic off-fault damage does develop during the earthquake rupture, with this ...…”
Section: Introductionmentioning
confidence: 99%
“…Although they are based on different formalisms, all these models confirm that significant coseismic off-fault damage does develop during the earthquake rupture, with this development markedly affecting the mode and properties (i.e., speed and directivity) of the dynamic rupture and the seismic radiation. However, none of these studies have addressed the question of earthquake slip profiles; either the slip distributions that emerge from the experiment or modeling are not examined [Sammis et al, 2009;Hok et al, 2010;Suzuki, 2012;Xu and Ben-Zion, 2013;Gabriel et al, 2013] or they are examined yet found to be different from natural, generic slip profiles [Andrews, 2005;Dunham and Rice, 2008;Templeton and Rice, 2008;Dieterich and Smith, 2009;Savage and Cooke, 2010;Griffith et al, 2010;Dunham et al, 2011aDunham et al, , 2011bXu et al, 2012a].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have characterized fault‐zone damage [e.g., Kim et al , 2004; Manighetti et al , 2004; Ben‐Zion and Sammis , 2003] and some have provided rheology models to describe the evolution of damage and fault zones [e.g., Lyakhovsky et al , 1997; Nanjo et al , 2005, and references therein]. Recent studies have also accounted for material‐degradation in models of long‐term fault evolution and seismicity patterns [ Finzi et al ,2009; Lyakhovsky and Ben‐Zion , 2008; Duan and Oglesby , 2005], and others addressed the effect of off‐fault damage on ruptures [ Ma and Andrews , 2010; Hok et al , 2010]. However, to date none has combined off‐fault damage in step‐over zones and rupture dynamic simulations to yield insights into the stability of segmented fault‐systems.…”
Section: Introductionmentioning
confidence: 99%